PERANCANGAN SISTEM INFORMASI MANAJEMEN DATA OBAT BERBASIS WEB DI UPTD INSTALASI FARMASI DINAS KESEHATAN KOTA JAMBI - M. Zalvien Haviz; Ahmad Nasukha; Albet Triadi (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The programming language used in this web development is PHP using the Laravel framework and the RDBMS used is MySQL. The system development model used is the SDLC waterfall model so that the work is gradual and more structured. This research resulted in web-based drug management at the Jambi City Pharmaceutical Installation UPTD being able to solve the problem of recording incoming drugs from Pharmaceutical Wholesalers, Submission of LPLPO files by Puskesmas as official proof of drug needs at the Puskesmas, outgoing drugs during drug distribution activities to Puskesmas, data on Pharmaceutical Wholesalers who partner as drug suppliers at the Jambi City. Health Office Pharmaceutical Installation UPTD Warehouse, data on health centers in Jambi City along with officers who will come during distribution and drug data that will be returned to the Pharmaceutical Wholesaler responsible for the product.